Effect of different drying methods on some mineral elements, amino acids and fatty acids of the fruits of some Iraqi palm cultivars - RAMIA SHEHAB HAMZA; ALAA GAZI AL-HASHIMI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hamza RS, Al-Hashimi AG. 2023. Effect of different drying methods on some mineral elements, amino acids and fatty acids of the fruits of some Iraqi palm cultivars. Biodiversitas 24: 359-369. The current study aimed to produce date palm powder from low-quality local varieties, namely (Dayeri and Zahdi). The dates were dried by three methods (solar, electric and microwave) and the mineral elements of the date powder were investigated. The mineral components in the powder produced by heat treatments increased significantly, although the microwave was the best drying method. The microwave-dried Dayeri date powder had the highest levels of potassium and phosphorus, whereas the microwave-dried Zahdi showed the highest levels of calcium. A discrepancy was observed in the saturated and unsaturated fatty acids of date powder, diagnosed by gas chromatography connected to a mass spectrometer. Fatty acid levels were affected by heat treatments, a decrease in saturated and unsaturated fatty acids was recorded, especially by the electric oven drying method. Amino acids ratio varied between varieties and drying methods; the dates of the Zahdi variety contain the highest percentage of amino acids. The proline amino acid was superior to the other amino acids; the solar-dried Zahdi powder had the highest concentration of proline, while the microwave-dried powder had higher concentrations of leucine and serine. Similar amounts of phenylalanine and threonine were found in Zahdi powder that had been microwave dried. However, the amount of cysteine in that which had been solar-dried was higher. The objective of the current study is to determine some biochemical constituents of the locally considered low-quality dates in southern Iraq. These date varieties have not been investigated before for their nutritional quality.